Pozyskanie Giovanniego Mavera dla polonistyki włoskiej - Rabenda, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The subject of the article is an attempt at recreating, based on source material, the initial contacts of the renowned Slavist Giovanni Maver with the studies of Polish literature in Poland and the community around two scholars in Polish literature: Stanisław Kot and Roman Pollak.